2004
DOI: 10.1016/j.otohns.2004.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss with Semicircular Canal Transection and Pseudomonas Aeruginosa Otitis Media

Abstract: Factors unique to PA infection may be responsible for SNHL with labyrinthine injury in humans with chronic otitis media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Prevatt et al (2004) demonstrated that P. aeruginosa in the middle ear may increase the risk of sensorineural hearing loss. Using an animal model in guinea pigs, the authors concluded that rupture of the tympanic membrane with the presence of P. aeruginosa in the middle ear was associated with a significant risk of sensorineural hearing loss in the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Prevatt et al (2004) demonstrated that P. aeruginosa in the middle ear may increase the risk of sensorineural hearing loss. Using an animal model in guinea pigs, the authors concluded that rupture of the tympanic membrane with the presence of P. aeruginosa in the middle ear was associated with a significant risk of sensorineural hearing loss in the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, P . aeruginosa is associated with keratitis [ 11 ] and chronic suppurative otitis media [ 12 ] leading to visual impairment and deafness [ 13 , 14 ]. P .…”
Section: Introductionmentioning
confidence: 99%
“…13 Additionally, the hearing loss appears to be primarily sensorineural with little or no conductive component. 14 Infection with Pseudomonas aeruginosa (PA) has been shown to be an important part of the development of hearing loss, 15 whereas hearing loss due to injury in the presence of other bacteria is more inconsistent. 16 …”
Section: Introductionmentioning
confidence: 99%